The Women's Dual Roles: Case Study of Informal Sector Working Mothers - Istiyana Afifah; Dhea Arisati; Nanindhita Nur Khasanah; Desti Nadya Amanda; Rizqan Kariema Mustafa (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
In many Global South societies, especially in Southeast Asia, women are increasingly burdened with dual responsibilities in the informal economy and domestic sphere. This phenomenon of dual roles often leads to role conflict, disproportionately affecting women’s well-being due to persistent gendered expectations and structural inequalities. This study aims to explore how women navigate these conflicts in contexts shaped by patriarchal norms and economic precarity. Using a qualitative phenomenological method, the research draws insights from in-depth interviews with three women workers in the informal sector in Jember, Indonesia, who also bear domestic responsibilities. The findings reveal that these women face significant role strain due to the unequal division of labor at home, although some receive minimal support from their spouses. Despite these challenges, women continue to strive for balance between productive and reproductive labor. Framed by feminist theory and situated within Global South epistemologies, this study highlights how gender inequality is reproduced through everyday practices. It also calls for more context-sensitive policies that recognize and support the invisible labor of women in informal sectors across the Global South.